Use of Kahoot media and variations of questions on learning achievement with motivation as moderation - Bila Anggraini; Nurdin Nurdin; Pujiati Pujiati (Lighthouse Publishing, 2021)
This study aims to determine whether there is an influence of the use of Kahoot and the variation of questions on learning achievement with motivation as a moderator. The populations were the tenth-grade students of social sciences at SMA Negeri 1 Sumberejo in the 2019/2020 academic year, with a sample of 81 students determined using a Cochran formula. The study adopted a descriptive verification method with ex-post facto and survey approaches. The collected data were analysed using a linear regression test with path analysis. The results indicate that there is an influence of the use of Kahoot media, the variation of questions, and learning motivation on the economic learning achievement among the tenth-grade students of social sciences at SMA Negeri 1 Sumberejo in the academic year of 2019/2020.